Ludowy bohater i ludowy widz. Społeczno-kulturowe źródła filmowych preferencji polskiej widowni - Giza, Barbara; Wenzel, Michał (Załącznik Kulturoznawczy, 2024)
The article presents the results of the study “Poles about Polish films. Opinions of Poles of the Polish Cinema and their Attitudes towards Polish Film Production. Social Research”, which was conducted in 2021 by the National Film Archive – Audiovisual Institute. We focus on the preferences of television viewers, indicating their favorite “countryside” films, especially the trilogy All Friends Here by Sylwester Chęciński. We attempt to interpret such audience choices through the strong roots Polish society has in the countryside, both in terms of origin and cultural habits.